Use, Mention, and Tangles Around Truth - Corey Dethier (Baltic International Yearbook of Cognition, Logic and Communication, 2026)
I extend Azzouni’s discussion of use/mention errors, highlighting three examples with a common theme: the systematic over-inflation of the concept of truth.